Storage and transformation of organic matter fractions in cryoturbated permafrost soils across the Siberian Arctic - N. Gentsch (Institute of Soil Science, Leibniz Universität Hannover); R. Mikutta (Institute of Soil Science, Leibniz Universität Hannover); R. J. E. Alves (Department of Ecogenomics and Systems Biology, Faculty of Life Sciences, University of Vienna); J. Barta (Department of Ecosystems Biology, University of South Bohemia); P. Čapek (Department of Ecosystems Biology, University of South Bohemia); A. Gittel (Center for Geomicrobiology, Aarhus University); G. Hugelius (Department of Physical Geography and Quaternary Geology, Stockholm University); P. Kuhry (Department of Physical Geography and Quaternary Geology, Stockholm University); N. Lashchinskiy (Central Siberian Botanical Garden, Siberian Branch of Russian Academy of Sciences); J. Palmtag (Department of Physical Geography and Quaternary Geology, Stockholm University); A. Richter (University of Vienna); H. Šantrůčková (Department of Ecosystems Biology, University of South Bohemia); et al. (Biogeosciences, 2015)
The abstract is available here: https://uscholar.univie.ac.at/o:446794 The abstract is available here: https://uscholar.univie.ac.at/o:446794